Nonparametric rank tests for non-stationary panels - Peter Pedroni; Timothy J. Vogelsang; Martin Wagner; Joakim Westerlund (Institute for Advanced Studies (IHS), 2011)
This study develops new rank tests for panels that include panel unit root tests as a special case. The tests are unusual in that they can accommodate very general forms of both serial and cross-sectional dependence, including cross-unit cointegration, without the need to specify the form of dependence or estimate nuisance parameters associated with the dependence. The tests retain high power in small samples, and in contrast to other tests that accommodate cross-sectional dependence, the limiting distributions are valid for panels with finite cross-sectional dimensions.
Keywords: C12; C22; C23; 330; nonparametric rank tests; unit roots; cointegration; cross-sectional dependence